Construction of an underwater plasma and Fenton hybrid system for the rapid oxidation of organic dyes and antibiotics. (April 2023) - Kim, Soo Hyeon; Seo, Jiwon; Hong, Yongcheol; Shin, Yongwook; Chung, Hea-Jong; An, Ha-Rim; Kim, ChangYeon; Park, Ji-In; Lee, Hyun Uk
Abstract: In this study, the decomposition efficiency and oxidation rate of organic pollutants were improved using a combination of a dielectric barrier discharge (DBD) plasma system and Fe3 O4 Fenton catalyst, a representative advanced oxidation process (AOP). The combined plasma Fenton system showed >99 % degradation of 200 mg L −1 dyes within 35 min, while other AOP systems achieved lesser degradation of the same concentration of dyes in 40 min: no degradation in the Fe3 O4 Fenton system and <25 % in the Ozone(O3 ) system. Additionally, >92 % of tetracycline and ciprofloxacin (TC, CIP: 10 mg L −1 ) was effectively degraded in the plasma Fenton system within 5 min, in contrast to the Fe3 O4 Fenton system. The rapid degradation of organic compounds was attributed to various oxidant species, including O3, H2 O2, and OH, from the reaction between the plasma electrode and Fenton catalyst. By analyzing chemically active species and interfacial reactions of the multiple-hole DBD underwater plasma Fenton system, we improved the accessibility of AOP element technology and proposed a research foundation for the decomposition reaction, thereby providing a theoretical basis for developing this technology.